NEP 2020 and Environmental Studies (EVS) Curriculum - Sharma, Kavita; Sharma, Purnima (Voices of Teachers and Teacher Educators, 2021)
Based on the National Policy on Education, the National Curriculum Frameworks offer recommendations for the curriculum, pedagogical strategies, and instructional materials for many topics at all educational levels in India. The third policy in India since independence, the recently announced National Education Policy (NEP 2020), aims to modernize every facet of education in order to envision an educational system. It builds upon India’s traditional and value system while including the framework, rules, and governance of 21st century education, including Sustainable Development Goal (SDG) 4.